Analysis of energy security level in the Baltic States based on indicator approach. (15th May 2020) - Augutis, Juozas; Krikštolaitis, Ričardas; Martišauskas, Linas; Urbonienė, Sigita; Urbonas, Rolandas; Ušpurienė, Aistė Barbora
Abstract: Energy security for small countries like Estonia, Latvia and Lithuania, which are called the Baltic States, is vital for ensuring energy independence and is a driving force for the development of a strong economy. The aim of the study presented in this paper is an analysis of the Baltic States regarding the performance of energy security level based on indicators. The analysis covers 2008–2016, in which the Baltic States faced essential changes in the energy sector. The methodology, based on indexes, is adopted for an integral measure of energy security level. The system of indicators is proposed, which considers technical, economic, geopolitical and sociopolitical aspects of energy security. The indicator system using statistical data is applied to each Baltic State, which enables evaluation of energy security level. The application of the developed model demonstrates which measures strengthen energy security. The results demonstrate that the energy security level of Estonia and Latvia is higher in comparison to Lithuania. The main factors for these differences are that Estonia and Latvia have strong own energy resources, such as oil shale and hydropower respectively, while Lithuania is characterized by high level of electricity import. Highlights: Analysis of energy security level in the Baltic States is presented. The system of energy security indicators is proposed. The energy security level for the Baltic States considerably increased during 2008–2016. Estonia and Latvia demonstrate higher energy security comparing to Lithuania.